ULTRASTRUCTURAL CHANGES OF THE ADENOGIPOPHYSIS INTERMEDIATE PART UNDER LONG-TERM ACTION OF NITRATES AND MEANS OF CORRECTION BY METHYLENE BLUE - Chumachenko, O.Yu.; Redka, O.G.; Cherno, V.S. (World of Medicine and Biology, 2021)
The perpose of the work was to study the ultrastructural changes of melanotropic cells in the intermediate part of the adenohypophysis in 14-, 45- and 90-day-old rats under the action of nitrates and correction with methylene blue. The results of the study showed that the simultaneous action of nitrates and methylene blue had a positive effect on the structure and function of melanotropic cells of the intermediate lobe of the adenohypophysis in all periods of the study. Methylene blue mitigated their toxic effect on melanotropics of the adenohypophysis intermediate and was a kind of protector of nitrates, reducing the manifestation of the depletion stage of the general adaptation syndrome and helping to restore hormonal balance in the intermediate adenohypophysis. The obtained results open the prospect of further study of structural and functional changes patterns in the endocrine glands under nitrate intoxication and provide a basis for developing effective and safe preventive measures to correct endocrine disorders in humans as a result of professional activities.